Beyond counting climate consensus - Pearce, Warren; Grundmann, Reiner; Hulme, Mike; Raman, Sujatha; Hadley Kershaw, Eleanor; Tsouvalis, Judith (Taylor and Francis, 2017)
Several studies have been using quantified consensus within climate science as an argument to foster climate policy. Recent efforts to communicate such scientific consensus attained a high public profile but it is doubtful if they can be regarded successful. We argue that repeated efforts to shore up the scientific consensus on minimalist claims such as ‘humans cause global warming’ are distractions from more urgent matters of knowledge, values, policy framing and public engagement.  Such efforts to force policy progress through communicating scientific consensus misunderstand the relationship between scientific knowledge, publics and policymakers. More important is to focus on genuinely controversial issues within climate policy debates where expertise might play a facilitating role. Mobilising expertise in policy debates calls for judgment, context and attention to diversity, rather than deferring to formal quantifications of narrowly scientific claims.